Investigation of phosphoproteome in RAGE signaling - Batkulwar, Kedar B.; Bansode, Sneha B.; Patil, Gouri V.; Godbole, Rashmi K.; Kazi, Rubina S.; Chinnathambi, Subashchandrabose; Shanmugam, Dhanasekaran; Kulkarni, Mahesh J. (Proteomics, 2015)
The receptor for advanced glycation end products (RAGE) is one of the most important proteins implicated in diabetes, cardiovascular diseases, neurodegenerative diseases, and cancer. It is a pattern recognition receptor by virtue of its ability to interact with multiple ligands, RAGE activates several signal transduction pathways through involvement of various kinases that phosphorylate their respective substrates. Only few substrates have been known to be phosphorylated in response to activation by RAGE (e.g., nuclear factor kappa B); however, it is possible that these kinases can phosphorylate multiple substrates depending upon their expression and localization, leading to altered cellular responses in different cell types and conditions. One such example is, glycogen synthase kinase 3 beta which is known to phosphorylate glycogen synthase, acts downstream to RAGE, and hyperphosphorylates microtubule-associated protein tau causing neuronal damage. Thus, it is important to understand the role of various RAGE-activated kinases and their substrates. Therefore, we have reviewed here the details of RAGE-activated kinases in response to different ligands and their respective phosphoproteome. Furthermore, we discuss the analysis of the data mined for known substrates of these kinases from the PhosphoSitePlus (http://www.phosphosite.org) database, and the role of some of the important substrates involved in cancer, diabetes, cardiovascular diseases, and neurodegenerative diseases. In summary, this review provides information on RAGE-activated kinases and their phosphoproteome, which will be helpful in understanding the possible role of RAGE and its ligands in progression of diseases.
Keywords: Cell biology; Disease; Glycation; Kinase; Phosphoproteome; RAGE

N-(3-Aminoalkyl)proline derivatives with potent antigycation activity - Chilukuri, Harsha; Kolekar, Yogesh M.; Bhosle, Govind S.; Godbole, Rashmi K.; Kazi, Rubina S.; Kulkarni, Mahesh J.; Fernandes, Moneesha (RSC Advances, 2015)
The importance of amino acids in the therapy of conditions such as renal failure, neurological disorders and congenital defects has been documented. Some amino acids such as lysine and glycine have also been reported to have antiglycating activity. Herein we report the synthesis of a new series of N-(3-aminoalkyl)proline derivatives which are non-natural in nature. The compounds were unambiguously characterized by NMR, mass and IR spectroscopy. Their in vitro antiglycation activity was studied by circular dichroism and fluorescence spectrometry. The mechanism of action was also studied and found to take place by inhibition of Amadori product formation. The inhibition of AGE formation was further confirmed by western blot and LC-MS/MS analyses and the IC50 values of the potent compounds were determined. Compounds containing hydroxyl substituents at C4 were found to have superior antiglycation properties than those containing azide substituents at the same position. The compounds were additionally found to possess good anti-oxidant properties, which could lead to further reduction in AGE formation. Moreover, the title compounds were found to have low cytotoxicity in mammalian cells, another important attribute. Thus, the title compounds represent a novel promising class of antiglycating agents.

Role of tumor cell surface lysosome-associated membrane protein-1 (LAMP1) and its associated carbohydrates in lung metastasis - Agarwal, Akhil Kumar; Srinivasan, Nithya; Godbole, Rashmi K.; More, Shyam K.; Budnar, Srikanth; Gude, Rajiv P.; Kalraiya, Rajiv D. (Journal of Cancer Research and Clinical Oncology, 2015)
Expression of lysosome-associated membrane protein-1 (LAMP1) on the surface correlates with metastatic potential of B16 melanoma cells. Downregulation of their expression in high metastatic (B16F10) cells reduced their surface expression and metastatic potential. Present investigations explore if overexpression of LAMP1 on the surface of low metastatic (B16F1) cells augment their metastatic ability, and if so, how? B16F1 cells were transduced with lentiviral vector carrying mutant-LAMP1 (Y386A) (mutLAMP1). Surface expression of LAMP1 and carbohydrates was analyzed by flow cytometry, immunofluorescence and/or immunoprecipitation and Western blotting. Cell spreading and motility were assessed on components of extracellular matrix (ECM) (fibronectin) and basement membrane (BM) (matrigel), and galectin-3-coated coverslips/plates. Metastatic potential was assessed using experimental metastasis assay. Pre-incubation with anti-LAMP1 antibodies significantly reduced lung metastasis of B16F10 cells. Overexpression of mutLAMP1 significantly increased its surface expression on B16F1 cells, resulting in increased cellular spreading and motility on fibronectin and matrigel. LAMP1 is the major carrier of poly-N-acetyllactosamine (polyLacNAc) on B16F10 cells. However, significantly higher expression of mutLAMP1 had no effect on galectin-3 binding on cell surface or on spreading or motility of cells on galectin-3-coated coverslips/plates. These cells also failed to show any gain in metastatic ability. This could be because LAMP1 from these cells carried significantly lower levels of polyLacNAc in comparison with B16F10 cells. PolyLacNAc on B16F10 cells and galectin-3 on lungs are the major participants in melanoma metastasis. Although surface LAMP1 promotes interactions with organ ECM and BM, carbohydrates on LAMP1 play a decisive role in dictating lung metastasis.
Keywords: 6 branched N-oligosaccharides; beta 1; Cell surface LAMP1; Galectin-3; Motility; Organ-specific metastasis; Poly-N-acetyllactosamine

Hydralazine inhibits amyloid beta (Aβ) aggregation and glycation and ameliorates Aβ1–42 induced neurotoxicity - Batkulwar, Kedar B.; Jana, Asis K.; Godbole, Rashmi K.; Khandelwal, Puneet; Sengupta, Neelanjana; Kulkarni, Mahesh J. (RSC Advances, 2016)

Mass spectrometry based identification of galectin-3 interacting proteins potentially involved in lung melanoma metastasis - Dange, Manohar C.; Bhonsle, Hemangi S.; Godbole, Rashmi K.; More, Shyam K.; Bane, Sanjay M.; Kulkarni, Mahesh J.; Kalraiya, Rajiv D. (Molecular Biosystems, 2017)
Adhesive interactions between molecules on tumor cells and those on target organs play a key role in organ specific metastasis. Poly-N-acetyl-lactosamine (polyLacNAc) substituted N-oligosaccharides on melanoma cell surface glycoproteins promote lung specific metastasis via galectin-3 by facilitating their arrest and extravasation. This study reports the identification and characterization of galectin-3 interacting proteins using a combination of galectin-3 sepharose affinity and leucoagglutinating phytohemagglutinin (L-PHA) columns. A total of 83 proteins were identified as galectin-3 interacting glycoproteins, of which 35 were constituents of the L-PHA bound fraction, suggesting that these proteins carry polyLacNAc substituted beta 1,6 branched N-glycans. The identities of some of these proteins, like LAMP-1, LAMP-3, basigin, embigin, and alpha 5 and beta 1 Integrin, have been confirmed by western blotting, and functional relevance with respect to metastatic properties has been established.